Unravelling "off-target" effects of redox-active polymers and polymer multilayered capsules in prostate cancer cells - Beretta, Giovanni L.; Folini, Marco; Cavalieri, Francesca; Yan, Yan; Fresch, Enrico; Kaliappan, Subramanian; Hasenhoerl, Christoph; Richardson, Joseph J.; Tinelli, Stella; Fery, Andreas; Caruso, Frank; Zaffaroni, Nadia (Nanoscale, 2015)
Redox-active polymers and carriers are oxidizing nanoagents that can potentially trigger intracellular off-target effects. In the present study, we investigated the occurrence of off-target effects in prostate cancer cells following exposure to redox-active polymer and thin multilayer capsules with different chemical properties. We show that, depending on the intracellular antioxidant capacity, thiol-functionalized poly(methacrylic acid), PMASH triggers cell defense responses/perturbations that result in off-target effects (i.e., induction of autophagy and down-regulation of survivin). Importantly, the conversion of the carboxyl groups of PMASH into the neutral amides of poly(hydroxypropylmetacrylamide) (pHPMASH) nullified the off-target effects and cytotoxicity in tested cell lines. This suggests that the simultaneous action of carboxyl and disulfide groups in PMASH polymer or capsules may play a role in mediating the intracellular off-target effects. Our work provides evidence that the rational design of redox-active carriers for therapeutic-related application should be guided by a careful investigation on potential disturbance of the cellular machineries related to the carrier association. This journal is
CRIS-Team Scopus Importer:2023-03-20